Regenerating physical development of non-conventional (religious) education in Perak - Mohamed Osman, Mariana; Bachok, Syahriah; Ahmad Thani, Siti Nur 'Alia; Ibrahim, Mansor (Elsevier, 2015)
The provision of Islamic school is essential in Malaysia as the majority of the population (64%) is Muslim. The purpose of this paper is to identify types of Islamic School and school facilities in Perak and area regeneration contribution to the school. The methods adopted for this study are document analysis and survey questionnaire that had been distributed to the parents and teacher of the Islamic school. The result indicates that the respondent agreed that facilities provided at the Islamic school are inadequate. Findings from this research highlight government and school management roles in managing inadequate facilities in the school.